Does Corporate Social Performance (CSP) Matter After the Financial Crisis? - Zulfikar Ali Ahmad; Fachmi Pachlevi Yandra (Ijtimā`iyya: Journal of Muslim Society Research, 2020)
This study aims to examine whether corporate social performance (CSP) increase after the crisis period. This study also examined whether CSP in the Jakarta Islamic Index (JII) member better than non-member JII. The content analysis method was used, and CSP data was measured using the item developed by Michael Jantzi Research Associate (MJRA) Inc. MJRA made a comprehensive measurement for measuring CSP. It dimensions consist of community issues, workplace diversity, environmental performance, employee relations, international issues, business practices and products, and others. The samples on this study are manufacturing companies listed in Indonesia Stock Exchange after the crisis period, 2009-2010. The result indicated that CSP in 2010 higher than in 2009. CSP in the member of JII also better than non-members of JII. This result indicated that CSP was relevant to the Jakarta Islamic Index member even after a crisis period.